Is my footprint too big? Exploring the ecological footprint concept with high school students. (2nd October 2018) - Karaarslan Semiz, Güliz; Çakır Yıldırım, Birgül
Abstract: The ecological footprint concept is important in order to evaluate the human impact on the environment and propose sustainable solutions in our life. By calculating ecological footprint, people could analyze the impact of their lifestyle on the natural environment. The purpose of this study is to share an ecological footprint education module for high school students in order to increase their awareness and understanding related to this concept. This module included theoretical and activity parts and was applied to 140 ninth-grade high school students. Through the activity, students could understand the connection between ecological footprint, bio-capacity, and population and explore how our actions influence our ecological footprint and bio-capacity. Teachers could adapt this ecological footprint education module so that their students could understand the connection between human activities and earth systems.